Dinosaur vs. bedtime - Shea, Bob. (New York : Disney/Hyperion Books, 2011)
A young dinosaur takes on many challenges and wins every time. Then Dinosaur faces his toughest challenge of all: bedtime.
A Junior Library Guild selection
Ages 2-5.
Keywords: Board books; Dinosaurs -- Picture books; Bedtime -- Picture books; Dinosaurs -- Fiction; Bedtime -- Fiction; Board books for children; Board books